Integrated Marketing Communications in Risk and Crisis Contexts a Culture-Centered Approach - Littlefield, Robert S. (Integrated marketing communication (Lanham, Md.), 2021)
Integrated Marketing Communications in Risk and Crisis Contexts introduces risk and crisis within the context of IMC, the culture centered approach to communicating with multiple publics, and applies the IDEA Model for effective message construction. Case studies illustrate cultural approaches, along with an ethical framework for communication.